Social Competence and its relationship to psychological stress among university students (A Field study at a sample students from Tishreen University( - الجهني, ريم; سليمان, هبة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to know the level of social competence and the level of psychological stress, the relationship of Social Competence to psychological stress among a sample of first year students at Tishreen University. It also aimed to reveal the differences in the level of Social Competence and psychological stress among The study sample according to the variety of sex and residency .Social Competence scale by (Abo Rumman,2008) was used in order to achieve the aims of the research, and psychological stress scale among university students which was designed by ( Al Hajjar and Dukhan ,2005),they were used after verifying their validity and reliability in the current research. The study sample consisted of (445) male and female students from the first year students from different colleges at Tishreen University . The results of the research showed that the level of Social competence among the members of the research sample was average, as well as the level of the competence on each dimension with average degree except for its level on the dimension compliance with laws ,which came with a high degree. Also, the level of psychological stress of the the research sample is average on the scale as a whole and on its dimension, and high on the dimensions dimensions( family pressure, personal pressure and social pressure. The existence of an inverse statistically correlation relationship with statistical significance between the total scores of the research sample on the social competence scale and their total scores on the psychological stress scale except for dimension the university environment pressure. A statistically significant differences was found between the mean score of the research sample on the Social Competence scale due to gender variable in favor of males except for dimension compliance with law and authority and matters related to security and safety. A statistically significant difference was found between the mean scores of the research sample on psychological stress scale due to the gender variable in favor of males except for two dimensions of study pressures and the university environment pressure .A statistically significant difference was found between the mean scores of the research sample on the Social Competence scale according to the residence variable for students from within the governorate .Also, found statistically significant differences between the mean scores of the research sample on psychological stress scale according to the residence variable for students in the university housing.